Experimental assessment of electromigration properties of background electrolytes in capillary zone electrophoresis - Bousková, Eva; Presutti, Carla; Gebauer, Petr; Fanali, Salvatore; Beckers, Jozef L; Bocek, Petr (Electrophoresis, 2004)
Electromigration dispersion (EMD) properties of background electrolytes (BGEs) used in capillary zone electrophoresis (CZE) are of key importance for the success of an analysis. The knowledge of these properties may serve well for the prediction of the asymmetry of peaks of analytes, for the prediction of unsafe regions where a strong interference of system zones may be expected, and for the selection of optimum conditions where the analytes of interest may give sharp and practically symmetric peaks. Present theories enable one to calculate and predict EMD properties of many BGEs but there is also a lot of BGEs that are beyond the present theoretical models as far as their composition and equilibria involved are considered. This contribution brings a method for assessment of EMD properties of any BGE from easily accessible experimental data. The method proposed is illustrated by model examples both for cationic and anionic separations. Imidazole acetate, histamine acetate, and histidine acetate served as model BGEs for cationic separations; as the model BGE for anionic separations, Tris-borate and sodium-borate BGEs have been selected since these buffers are frequently used and borate is well-known for its complexing equilibria in aqueous solutions.
Keywords: Acetates; ionty; Electrolytes; Imidazoles; Ions; elektrolyty; Histamine; histamin; acetáty; pufry; Buffers; Electrophoresis, Capillary; Histidine; histidin; elektroforéza kapilární; imidazoly